KAJIAN YURIDIS TERHADAP INVESTASI GADAI EMAS DI PERBANKAN SYARIAH - M KHARRAZI; BISMAR NASUTION; MAHMUL SIREGAR (Universitas Sumatera Utara, 2013)
One of the banks that have Islamic sharia pawning gold products, commonly known as the Golden Pawn Bank Syariah Mandiri which binding financing using qardh agreement in order rahn. Funding is provided to customers who have gold and need money immediately. This is evident from the rise of sharia pawning gold (rahn) who allegedly deviated from its original purpose. This concern arises because sharia should bertumpuh lien on Islamic principles which the essence is to help people to get funds quickly and for working capital. In practice, sharia pawning gold began to leave the essence and more widely used for profit through repeated practice of speculative mortgage. The research was conducted using the method of normative legal research or legal research literature, the data used are the primary legal materials, secondary, and tertiary, while the data collection is done with the study of literature (library researh). The method used in analyzing the data is qualitative analysis. Based on the results of the study authors that the legal basis for the gold investment in Islamic perspective is the verses of the Qur'an Surah Al-Baqarah (2) Section 283 is grounds relied upon in developing the concept of Islamic mortgage (Rahn). Hadith of the Prophet Muhammad in the hadith that Aisha riwayatkan by Muslim Faith, ijma 'ulama agreed on the permissibility of the legal status of liens, and the Islamic National Fatwa council chamber Ulama Indonesia (DSN-MUI) became one of the references relating to liens sharia (Rahn). Specifically with regard to sharia law lien (Rahn), MUI through the National Islamic council issued a fatwa No.: 25/DSN-MUI/III/2002. Arrangements relating to investment gold pawning at sharia banks namely, Bank Indonesia Regulation. 10/17/PBI/2008 On Islamic Banking products and Sharia that in order to avoid the risk of loss, the Islamic Bank and Islamic Business Unit obliged to maintain the quality of its financing, ne of the effort to maintain the quality of the financing, Islamic banks and Sharia can restructure financing of customers who have business prospects and / or ability to pay and estrukturisasi Financing Financing only be made for the quality of Substandard, Doubtful and Loss that must be supported by analysis and evidence of adequate and well- documented. Circular Letter of Bank Indonesia (SEBI) No.. 14/7/DpBs dated February 29, 2012 concerning the rules contributed to pawn gold pawn gold trigger for increased business, especially in Islamic banking. Given this rule, gold pawning business become more organized, and only for urgent short-term loans. No more gold for investment fiduciary practices. Keywords: Investasi, Gadai Emas